Widow Stigma: A Critical Study of the Discrimination of Widow in Public (Islamic Perspective and Gender) - Muhammad Aminuddin Shofi (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
This article aims to describe the stigma of the people of Tukum village, Tekung sub-district, Lumajang district towards women with widow status. It uses field research with a qualitative approach and an analysis of Islam and gender. The results are the emergence of negative perceptions of widow status because of male dominance in social life. They underestimate widowed women more easily than widowed men. Even though two widower statuses are the equivalent of widowed status because of the end of a divorce. However, there is also a positive stigma found by assuming that a widow cannot be underestimated. This is supported that there are widows who can be the backbone of their husbands after a divorce. Through gender analysis, differences in the image of widows were historically formed based on several factors. It was then socialized, strengthened, and built through socio-cultural, even supported by myths or religious misinterpretations. In Islam, the principle of justice is strongly upheld, equality of rights and obligations to men and women. They are adjusted to their respective responsibilities without preferences and discrimination that benefit men and harm women.